Toward A Simulation-Based Tool for the Treatment of Vocal Fold Paralysis - Mittal, Rajat; Zheng, Xudong; Bhardwaj, Rajneesh; Seo, Jung H.; Xue, Qian; Bielamowicz, Steven (Frontiers in Physiology, 2011)
Advances in high-performance computing are enabling a new generation of software tools that employ computational modeling for surgical planning. Surgical management of laryngeal paralysis is one area where such computational tools could have a significant impact. The current paper describes a comprehensive effort to develop a software tool for planning medialization laryngoplasty where a prosthetic implant is inserted into the larynx in order to medialize the paralyzed vocal-fold. While this is one of the most common procedures used to restore voice in patients with vocal-fold paralysis, it has a relatively high revision rate, and the tool being developed is expected to improve surgical outcomes. This software tool models the biomechanics of airflow-induced vibration in the human larynx and incorporates sophisticated approaches for modeling the turbulent laryngeal flow, the complex dynamics of the vocal folds, as well as the production of voiced sound. The current paper describes the key elements of the modeling approach, presents computational results that demonstrate the utility of the approach and also describes some of the limitations and challenges.